The Interruption of inferior vena cava in treatment of pulmonary thromboembolism: tecnique - Soto, José; Delgado, Bolívar; Gateño, Nisso (Cirugía del Uruguay, 1979)
Analysis of the different techniques employed in interruption and !igation of inferior vena cava, emphasizing the teclmique employed in Surgical Clinic "l" of the University of Montevideo, Medica! School and analyzing coi:nplications and sequela of this surgery.